An investigative study into school principals' leadership functions and their influence on a school's culture - Adra, Shereen (Beirut University of Balamand - Faculty of Arts and Social Sciences, 2013)
This investigative mixed-methodology research explores and examines some teachers' as well as some school principals' beliefs and perceptions about leadership attributes and all the complex interrelationships that exist between them and the dimensions of organizational culture. The study is mainly based on the theoretical framework created by Dimmock and Walker (2002). Instrumentation for data collection included a Likert-scale survey that encompassed 63 statements distributed to 97 teachers from 4 different schools, as well as four semi-structured interviews to elicit the four school principals' beliefs and perceptions about their own leadership functions and the organizational culture of their schools. Observation and document analysis were used as complementary methods. The main aim of this study is to investigate teachers' and school principals' beliefs, perceptions and attitudes towards educational leadership as well as organizational culture in four private schools in North Lebanon and to explore how school principals impact the culture of their schools. The results have shown that the four school principals do not employ leadership functions that build and nurture the kind of school culture they believe their schools to have.
: Mémoire
Keywords: Gestion scolaire; Leadership; Leadership; School management